A hefty dose of lemons: the importance of rituals for audiences and performers at the online Edinburgh Festival Fringe 2020. Issue 1 (2nd January 2022) - Piccio, Benedetta; Helgason, Ingi; Elsden, Chris; Terras, Melissa
ABSTRACT: When the pandemic began to affect the performance world, both festival artists and producers started to adopt creative approaches to moving their work online. In the study presented here, we focus on the 2020 Edinburgh Festival Fringe, which offered a unique opportunity to understand how performers coped with the enforced switch to digital. Underpinning the Fringe Festival ethos is the attitude of experimentation, and we propose that there is much to learn from the response of performers and producers to this unprecedented situation. As one interviewee put it; 'we got given a hefty dose of lemons, and the point of all of this was, just go and make lemonade and see what happens' (Yvette). In this article, we focus on the challenge of managing the audience experience in the digital space, particularly before and after a performance. We note that familiar rituals play a key role for physical audiences and we position this idea within the Trajectories Framework, identifying coherent journeys through a user experience (Benford and Giannachi 2011 . Performing Mixed Reality . The MIT Press. ISBN:978-0-262-01576-9), in order to frame it with digital audiences in mind. We provide recommendations regarding aspects for performers and producers to address as online and digital becomes an increasingly accepted part of the festival landscape.